Early Marriage in Hadith and Law: Analysis of Aisha’s Marriage and Legal Age Provisions - Muhammad Waliyuddin Yusuf; Imron Rosyadi (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
The phenomenon of early marriage remains a complex social and legal issue in Indonesia, illustrating the ongoing gap between religious texts, legal regulations, and social realities. This research departs from debates surrounding the hadith of the Prophet Muhammad’s marriage to ‘Aisha ra., which is often used as a religious justification for child marriage practices. The study aims to critically analyse the hadith through a socio-historical approach and the framework of maqāṣid al-sharī’ah, while assessing its conformity with Indonesian positive law. This research employs normative legal research with a qualitative perspective, relying on literature analysis of hadiths contained in Kutub al-Sittah, the views of classical Islamic jurists (fuqahā’), and national legal policies, particularly Law Number 16 of 2019 concerning the minimum marriage age. The findings reveal that classical scholars generally permitted marriage to al-ṣaghīrah based on specific historical and social contexts. However, contemporary scholars emphasise the need for contextual and purposive interpretation to ensure the protection of children from physical, psychological, and social harm. From the perspective of maqāṣid al-sharī’ah, this study highlights maṣlaḥah and harm prevention as fundamental legal principles. From a positive legal standpoint, setting the marriage age at 19 reflects harmonisation between Islamic law and child protection norms.